Application and Problems of Supervisors in the Implementation of Guidance and Counseling in Schools - Indah Wijayanti; Neviyarni S; Yarmis Sukur (Journal Of Psychology, Counseling And Education, 2025)
Guidance and counseling supervisors are employees of the Education Office who supervise and support the provision of guidance and counseling services in educational settings. Together with school principals, teacher supervisors and school administrators oversee guidance and counseling programs in schools. The BK coordinator organizes supervising teachers' preparation for supervision activities, including ensuring that they have sufficient resources and free time. Mentor teachers adhere to coaching and assessment procedures during supervision activities. To improve guidance and counseling standards, the principal supports and facilitates the implementation of objective and dynamic supervision activities.